THE GENE POOL FOR TABLE BEET BREEDING (MODERN ASPECTS OF STUDY AND USE) - V. I. Burenin; D. V. Sokolova; T. M. Piskunova (Труды по прикладной ботанике, генетике и селекции)
Background. Modern production imposes increased requirements to the range of used cultivars, so the development of new cultivars and hybrids most adapted to certain soil and climatic conditions is an important task of breeding.Materials and methods. Table beet accessions from the VIR collection originating from 17 countries were chosen as the material for the present research. The accessions were studied at Pushkin and Pavlovsk Laboratories of VIR, at the Genetic Diversity and Plant Bioresources Center of the All-Russian Breeding and Technological Institute of Horticulture and Nursery (VSTISP) and at Maikop Experiment Station, a branch of VIR, according to VIR’s guidelines. esults. The relationships between earliness, bolting resistance, cold tolerance and resistance to black root have been established. The majority of the studied accessions had medium resistance to black root. The cultivars ‘Asmer Detroit 72’ (k-3113, Great Britain), ‘Bravo’ (k-3047, Russia) and ‘Podzimnyaya A-474’ (k-1678, Russia) distinguished by resistance to black root, were also characterized by cold tolerance and stable productivity. The differences in bolting resistance among the accessions were found to depend on their origin. The cultivars from Sweden, Finland and from the Russian Northwest were most resistant to bolting. The early accessions ‘Perfected Detroit Dark Red’ (k-1815, Canada), ‘Bikor’ (k-2873, the Netherlands), ‘Severnyshar’ (k-1586, Russia) and ‘Polyarnaya ploskaya’ (k-1585, Russia) were characterized by high rates of the vegetative mass growth and bolting resistance. It was noted that the absolutely monogermic varieties have lower ripening rates, productivity, and resistance to bolting, compared to the multigerm ones, but have similar chemical composition indicators and root quality. Accessions with a wide distribution area that maintain high root productivity at 115–120% to the reference in different climatic conditions have been identified.Conclusions. The research has resulted in the identification of table beet accessions characterized by a complex of biological and economically important traits. The relationships between earliness, resistance to bolting and cold tolerance have been revealed. Genetic sources of monogermicity, bolting resistance, cold tolerance, black root resistance and high root quality are recommended for the use in breeding.